2015
DOI: 10.1200/jco.2015.61.2838
|View full text |Cite
|
Sign up to set email alerts
|

Coverage With Evidence Development and Managed Entry in the Funding of Personalized Medicine: Practical and Ethical Challenges for Oncology

Abstract: Personalized medicines hold promise for many diseases. However, demonstrating the clinical efficacy and cost effectiveness of these medicines can be difficult. It is essential that decision-making processes for funding new medicines, including personalized medicines, are both robust and fit for purpose. We will argue that randomized trials of personalized medicines should be routinely supplemented with other research methods, such as observational research and single-arm studies, and that managed-entry funding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…Randomized controlled trials are the cornerstone of evidence development in oncology; however, the applicability of the evidence generated from RCTs to real‐life populations will depend on the degree of alignment between the research and target population in terms of clinical and molecular characteristics . Although not a substitute for RCTs, RWR does offer the potential to supplement knowledge gaps and address questions that cannot be solved by clinical trials .…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials are the cornerstone of evidence development in oncology; however, the applicability of the evidence generated from RCTs to real‐life populations will depend on the degree of alignment between the research and target population in terms of clinical and molecular characteristics . Although not a substitute for RCTs, RWR does offer the potential to supplement knowledge gaps and address questions that cannot be solved by clinical trials .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (33) also examined the effectiveness of a number of cancer therapies approved by the FDA on the basis of surrogate endpoints and found that the majority of these had unknown or no effects on overall survival. The difficulties of withdrawal from the market or disinvestment from technologies that later prove to be unsafe, ineffective or less cost-effective than initially thought are also well-recognized (34). The recent changes to the UK's Cancer Drugs Fund (described above) and the current review of Australia's special fund for the reimbursement of treatments for rare diseases (the Life Saving Drugs Program) on the basis of sustainability (35) are other salient examples of the risks and opportunity costs associated with accelerated access.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Funding decisions in health systems that fund anticancer drugs significantly affect the practice of medical oncologists and the anticancer drugs that are accessible to patients. The rejection rate of initial submissions was nevertheless greater in the second half of the study period compared to the first.…”
Section: Pbac Rejection Of Anticancer Drugsmentioning
confidence: 99%